Experimental investigation of an elastic pendulum. (18th October 2017) - Cross, Rod
Abstract: A mass on the end of a spring can oscillate vertically, horizontally or both at the same time. Experimental observations are presented and simple explanations are given for the observed motion of the mass, including the well known case where the frequency of oscillation in the vertical direction is twice that for pendulum motion. In the latter case, measurements show that the horizontal restoring force on the mass is a nonlinear function of the horizontal displacement, causing the horizontal amplitude to grow with time. However, the vertical oscillation frequency then decreases due to a decrease in the vertical restoring force, causing the horizontal amplitude to decrease with time. The net result is a periodic transfer of energy between vertical and horizontal motion.